On the sense of the fourfold distinction of being in Aristotle - Tugendhat, Ernst; Másmela Arroyave, Carlos (Estudios de Filosofía, 1992)
"Being is said in many ways." This renowned statement presides over the project of the central treatise in Metaphysics, which extends from E2 to 810. The part of the text in which Aristotle says what he thinks with this statement, is, as is known, chapter 7. Here Areistotle put forward four meanings of ov eivat, and the second of these four is distinguished in turn into eight meanings, as many as there are categories. In the treatise E2-81O, Aristotle uses, when he refers to chapter 7, according to the need and the context, either the fourfold and broad distinction (1026a33ss, 1045b32, 1051a33ss.) or the eightfold internal subdivision of the 2nd meaning (1028a10ff.)